Keterampilan Menangkap Makna Artikel Ilmiah Jurnal Online melalui Google Forms - Damayanti, Welsi; Razak, Abdul; Hamidah, Siti (Universitas Terbuka, 2024)
The skill of reading comprehension of scientific articles in online journals is very important for students. Through this written literacy skill, students gain an understanding according to the focus and scope of the journal in question. This research is to review the Indonesian Language liberal art lectures when they are in their first year of college. The research uses a quantitative method by describing the score of the skill of capturing the meaning of scientific articles in online journals through parametric inferential statistical procedures. The research took place in the middle of the even semester of the 2022/2023 academic year. The subjects of this study were 83 students from the Indonesian Education University; divided into 29 students from the Communication Science Study Program, 26 students from the Physics Study Program, and 28 students from the Computer Science Study Program. The sample consisted of 69 students, divided into 24 students from the Communication Science Study Program, 22 students from the Physics Study Program, and 23 students from the Computer Science Study Program. The research instrument was in the form of a multiple-choice test via Google Forms media. The findings of the study: 1) the skill of reading comprehension of scientific articles in online journals via Google Forms media is in the moderate category; 2) there are differences in the skill reading comprehension of scientific articles in online journals via Google Forms media per sample group. Therefore, an effective strategy to improve students' meaning-making skills is written literacy skills with online media.